2004
DOI: 10.1029/2004gl020002
|View full text |Cite
|
Sign up to set email alerts
|

Silicon self‐diffusion in wadsleyite: Implications for rheology of the mantle transition zone and subducting plates

Abstract: [1] Si self-diffusion rates in Mg 2 SiO 4 polycrystalline wadsleyite were measured at 18 GPa and 1430 -1630°C using an isotopic tracer ( 29 Si) and secondary ion mass spectrometry. The volume diffusion coefficient (D v ) and grain-boundary diffusion coefficient (D gb ) were determined to be D v = 3.44 Â 10 À11 [m 2 /s] exp (À299 [kJ/mol]/RT) and dD gb = 1.14 Â 10 À17 [m 3 /s] exp (À248 [kJ/mol]/RT), respectively. Si diffusion rates in wadsleyite are about 5 orders of magnitude slower than Mg-Fe interdiffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…[] at ambient pressure, and other researchers [ Jaoul et al ., ; Houlier et al ., ; Andersson et al ., ; Béjina and Jaoul , ] (data not shown in Figure a). Nevertheless, the thermodynamic wadsleyite (10–20 GPa and 1000–1900 K) and ringwoodite (16–24 GPa and 1000–1900 K) calculations are slightly lower than those experimentally obtained [ Shimojuku et al ., ]. The experimental determinations for Si self‐diffusion in MgSiO 3 perovskite are completely close to each other [ Yamazaki et al ., ; Dobson et al ., ; Xu et al ., ] at 25 GPa.…”
Section: Resultscontrasting
confidence: 61%
“…[] at ambient pressure, and other researchers [ Jaoul et al ., ; Houlier et al ., ; Andersson et al ., ; Béjina and Jaoul , ] (data not shown in Figure a). Nevertheless, the thermodynamic wadsleyite (10–20 GPa and 1000–1900 K) and ringwoodite (16–24 GPa and 1000–1900 K) calculations are slightly lower than those experimentally obtained [ Shimojuku et al ., ]. The experimental determinations for Si self‐diffusion in MgSiO 3 perovskite are completely close to each other [ Yamazaki et al ., ; Dobson et al ., ; Xu et al ., ] at 25 GPa.…”
Section: Resultscontrasting
confidence: 61%
“…More recent experimental data by Dohmen et al [2002] showed a much higher activation energy for silicon diffusion in olivine compared to the older data. The new activation energy for olivine is also significantly different from the activation energy of silicon in wadsleyite [ Shimojuku et al , 2004]. However, silicon diffusion in wadsleyite is very similar to diffusivity of silicon in olivine reported by Houlier et al [1990].…”
Section: Applicationsmentioning
confidence: 91%
“…In our model, plate motion and plate-boundary migration are generated dynamically without velocity conditions imposed on the plate as our previous studies (Tagawa et al, 2007b;Nakakuki et al, 2008). We introduce the viscosity reduction in the transition-zone and/or the lower-mantle slab because of the grain-size reduction that accompanies the phase transitions at 410-km (Rubie, 1984;Karato, 1989;Riedel and Karato, 1997;Shimojuku et al, 2004;Yamazaki et al, 2005) and 660-km (Ito and Sato, 1991;Karato et al, 1995;Kubo et al, 2000) depths. The importance of the slab plasticity is highlighted in the mechanism that determines the structure and the fate of the subducted plate.…”
Section: Introductionmentioning
confidence: 99%